2013
DOI: 10.1200/jco.2012.44.4315
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of the Seventh Edition of the International Union Against Cancer Classification for Patients With Gastric Cancer: The Western Experience of Patients Treated in a Single-Center European Institution

Abstract: The seventh edition of the AJCC/UICC classification was found to be valid with distinctive prognosis for each stage. However, the AJCC/UICC classification has become more complex without improving predictability for overall survival in a Western population. Therefore, simplification with better predictability of overall survival of patients with gastric cancer should be considered when revising the seventh edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 33 publications
1
74
0
3
Order By: Relevance
“…Pathological assessment of gastrectomy specimens is an essential step in the evaluation of gastric cancer patients, allowing their categorization into groups with distinct treatment and prognosis [1][2][3][4][5]24]. During this analysis, small LNs are particularly difficult to find, and missing them may negatively impact the patient's life expectancy, since even micrometastasis reduces survival [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological assessment of gastrectomy specimens is an essential step in the evaluation of gastric cancer patients, allowing their categorization into groups with distinct treatment and prognosis [1][2][3][4][5]24]. During this analysis, small LNs are particularly difficult to find, and missing them may negatively impact the patient's life expectancy, since even micrometastasis reduces survival [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate staging is fundamental for prognosis and identification of those patients who should be referred for adjuvant therapy. The N status from the TNM classification strongly correlates with survival, and postoperative dissection of the specimen in the search for resected LNs should be diligently performed [1][2][3][4][5]. It is recommended that at least 16 LNs should be examined following a gastrectomy for gastric cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Rannsóknin er því samhljóma nýlegum rannsókn-um sem benda til þess að það að greinast með dreifkrabbamein samkvaemt Laurén-flokkun sé sjálfstaeður áhaettuþáttur fyrir verri horfum. 22,23,26 Talsverður hluti af meinunum var ekki stiganlegur, eða 25%, annaðhvort vegna þess að sjúkraskrárnar fundust ekki eða upplýsingarnar í sjúkraskránum voru ekki fullnaegjandi. Stigun byggir á myndgreiningu með tilliti til fjarmeinvarpa og lýsingu meinafraeðings í vefjasvörum brottnumins maga sem lýsir dýpt aexlis og því hvort meinvörp séu til staðar í eitlum.…”
Section: Umraeðurunclassified
“…Many others have also reported that N staging in 6th system is more optimal than that in the 7th system in Eastern populations [29,30,31]. Some suggest that the 7th system is more complex but does not improve the predictability for overall survival in Western populations [32,33]. In addition, there have been reports about the lack of information regarding the extent of lymph node dissection and difficulty in its application to surgical treatment planning with the N staging system.…”
Section: Uicc/ajcc Tnm Staging Systemmentioning
confidence: 99%